1999
DOI: 10.1017/s0950268899002666
|View full text |Cite
|
Sign up to set email alerts
|

An update on safety studies of SAD B19 rabies virus vaccine in target and non-target species

Abstract: SAD B19 is an attenuated vaccine virus for oral vaccination of carnivores against rabies. The safety of SAD B19 was investigated in 16 animal species by different routes of administration. During the observation period all animals given the vaccine virus, irrespective of the route of administration, did not show any clinical signs of rabies, with the exception of certain rodent species. In these animals a low residual pathogenicity was observed, however transmission of the vaccine virus to control animals was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
52
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 22 publications
0
52
0
Order By: Relevance
“…Very few studies investigated the presence of rabies virus in salivary glands of such cases, and if done, results were negative (as described below). Experimental studies on SAD B19 vaccine safety were undertaken by the manufacturer in 16 animal species (Vos et al 1999). No vaccine virus was detected in the saliva of vaccinated animals except in foxes, in which the virus was detected in the tonsils and parts of the mucosa up to 4 days postinoculation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies investigated the presence of rabies virus in salivary glands of such cases, and if done, results were negative (as described below). Experimental studies on SAD B19 vaccine safety were undertaken by the manufacturer in 16 animal species (Vos et al 1999). No vaccine virus was detected in the saliva of vaccinated animals except in foxes, in which the virus was detected in the tonsils and parts of the mucosa up to 4 days postinoculation.…”
mentioning
confidence: 99%
“…Brain and salivary glands, on the other hand, were negative. Despite attenuation, SAD Bern and SAD B19 are pathogenic for adult mice and other rodent species (Apodemus sp., Microtus sp., Mus musculus, Microtus epiroticus, Apodemus sylvaticus), whatever the route of inoculation (cerebral, muscular, or oral) (Artois et al 1992;Vos et al 1999). A laboratory study (Rupprecht et al 1990) demonstrated that the SAD B19 vaccine caused rabies in skunks (Mephitis mephitis) via the oral route.…”
mentioning
confidence: 99%
“…Compared with the other well-known attenuated strains such as SAD B19(a mortality of 5.8% to rat and 2% to mice) [13,14] ,SAG2 (nonpathogenic to 6 week old mice) [15] and SRV9 (nonpathogenic to 18-day-old mice) [16] ,the CTN181-3 and CTN181-19 showed a comparable low residual pathogenicity to them as 80% of 14-day-old suckling mice infected with a dose of 4.0lgPFU virus of CTN181-3 [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, immunoglobulin was entirely excluded from this study. Furthermore, the SADB19 has been reported safe for many carnivores irrespective of the route of administration (Vos et al, 1999). The SRV9, as a derivative of the SADB19, may also be safe for many carnivores and some species of mammals (Wei et al, 2010).…”
Section: Discussionmentioning
confidence: 99%